Stereotactic body radiotherapy is an effective treatment in reirradiating spinal metastases: current status and practical considerations for safe practice. Issue 12 (December 2011) - Masucci, Giuseppina Laura; Yu, Eugene; Ma, Lijun; Chang, Eric L; Letourneau, Daniel; Lo, Simon; Leung, Eric; Chao, Sam; Hyde, Derek; Gorgulho, Alessandra; Muacevic, Alex; Larson, David A; et al.
Spinal metastases are a relatively common manifestation in advanced cancer patients. Low-dose conventional radiotherapy has long been the mainstay of treatment under the assumption that patients have a limited life expectancy in the order of 3–6 months. However, with new developments in systemic therapies, patients are surviving longer than expected. As the spinal retreatment rates, secondary to conventional radiation, can approach 20–50%, retreatments are likely to be more frequent. Rather than a second course of even lower-dose conventional radiation, spine stereotactic body radiotherapy (SBRT) has been developed predominantly to overcome the limitations of conventional reirradiation. Spine SBRT permits a second course of high-dose radiation aimed at local tumor control while sparing the spinal cord, and other surrounding normal tissues, of a toxic dose. The focus of this review is to provide an overview of reirradiation spine SBRT, and address key issues surrounding safe and effective practice.